CRISPR Toolbox for Genome Editing in Dictyostelium - Yamashita, Kensuke; Iriki, Hoshie; Kamimura, Yoichiro; Muramoto, Tetsuya (Frontiers in Cell and Developmental Biology, 2021)
The development of new techniques to create gene knockouts and knock-ins is essential for successful investigation of gene functions and elucidation of the causes of diseases and their associated fundamental cellular processes. In the biomedical model organism Dictyostelium discoideum, the methodology for gene targeting with homologous recombination to generate mutants is well-established. Recently, we have applied CRISPR/Cas9-mediated approaches in Dictyostelium, allowing the rapid generation of mutants by transiently expressing sgRNA and Cas9 using an all-in-one vector. CRISPR/Cas9 techniques not only provide an alternative to homologous recombination-based gene knockouts but also enable the creation of mutants that were technically unfeasible previously. Herein, we provide a detailed protocol for the CRISPR/Cas9-based method in Dictyostelium. We also describe new tools, including double knockouts using a single CRISPR vector, drug-inducible knockouts, and gene knockdown using CRISPR interference (CRISPRi). We demonstrate the use of these tools for some candidate genes. Our data indicate that more suitable mutants can be rapidly generated using CRISPR/Cas9-based techniques to study gene function in Dictyostelium.